Waveguide optics in transition metal dichalcogenides visualized with near-field imaging - Mooshammer, Fabian; Xu, Xinyi; Trovatello, Chiara; Schuck, P. James; Basov, D. N. (International Conference on Infrared, Millimeter, and Terahertz Waves, IRMMW-THz, 2024)
We advance the potential of transition metal dichalcogenides for integrated photonics by exploring near-infrared waveguide optics in 3R-MoS2. The interference patterns of waveguide modes in nano-optical near-field images allow us to quantify the anisotropic dielectric tensor, providing essential parameters for phase-matched optical devices. Using a custom laser-patterning routine, we write gratings into van der Waals (vdW) slabs. Their functionality is verified by two experimental findings: the directional outcoupling of different waveguide modes and grating-coupled waveguide second-harmonic generation. Our work demonstrates the feasibility of compact frequency converters and examines the tunings knobs that enable optimized coupling into layered waveguides.
CRIS-Team Scopus Importer:2024-11-01
Keywords: gratings; laser patterning; near-field; nonlinear optics; van der Waals materials; waveguide